Nicotine in Inflammatory Diseases: Anti-Inflammatory and Pro-Inflammatory Effects - Zhang, Wenji; Lin, Hui; Zou, Mingmin; Yuan, Qinghua; Huang, Zhenrui; Pan, Xiaoying; Zhang, Wenjuan (Frontiers in Immunology, 2022)
As an anti-inflammatory alkaloid, nicotine plays dual roles in treating diseases. Here we reviewed the anti-inflammatory and pro-inflammatory effects of nicotine on inflammatory diseases, including inflammatory bowel disease, arthritis, multiple sclerosis, sepsis, endotoxemia, myocarditis, and oral, skin, and muscle inflammation, etc., mainly concerning the administration methods, different models, therapeutic concentration and duration, and relevant organs and tissues. According to the data analysis from recent studies in the past 20 years, nicotine exerts much more anti-inflammatory effects than pro-inflammatory ones, especially in ulcerative colitis, arthritis, sepsis, and endotoxemia. On the other hand, in oral inflammation, nicotine promotes and aggravates some diseases such as periodontitis and gingivitis, especially when there are harmful microorganisms in the oral cavity. We also carefully analyzed the nicotine dosage to determine its safe and effective range. Furthermore, we summarized the molecular mechanism of nicotine in these inflammatory diseases through regulating immune cells and immune factors and vagus and acetylcholinergic anti-inflammatory pathways. By balancing the “beneficial” and “harmful” effects of nicotine, it is meaningful to explore the effective medical value of nicotine and open up new horizons for remedying acute and chronic inflammation in humans.